The value of osteopontin in predicting fibrosis in patients with chronic viral hepatitis C - A.G. Sheiko; K.V. Yurko (Gastroenterologìa, 2023)
Background. Diagnosis of an asymptomatic course of chronic viral hepatitis C (HCV) and the existing development of the fibrotic process by determining the marker capabilities of biochemical blood parameters (primarily osteopontin — OP) is an urgent issue in modern medicine. Purpose: to evaluate the prognostic value of biochemical blood markers for diagnosing an asymptomatic course of HCV and the existing fibrotic process. Materials and methods. Seventy-eight people were examined: 47 from the main group — 19 (40.4 %) women and 28 (59.6 %) men with chronic HCV, and 31 controls — 17 (54.8 %) women and 14 (45.2 %) men without chronic HCV. The median, as well as 25.0% and 75.0% quartiles and relative values were calculated for quantitative and qualitative measures, respectively. Predictors were determined using logistic regression analysis. Results. The data obtained by a univariate analysis indicate a significantly increased risk of developing liver fibrosis on the background of chronic HCV, with alanine aminotransferase (ALT) levels increased by 1.037 times, aspartate aminotransferase (AST) by 1.051 times, gamma-glutamyl transferase (GGT) by 1.017 times; thymol turbidity test by 1.424 times; total protein by 1.162 times and OP by 3.002 times. With increased levels of triglycerides and very low-density lipoproteins, a significant decrease in these risks was found, by 74.7 and 94.7 %, respectively. A multivariate analysis found significantly increased risks of developing liver fibrosis on the background of chronic HCV, with higher levels of AST, total protein, and OP (by 1.028, 1.195 and 2.510 times, respectively). Conclusions. With a significant liver damage by a fibrotic process (stage 3–4), as compared to stage 0–2, there is a probable predominance of biochemical liver markers in the blood of patients with HCV: ALT, AST, GGT, total protein and OP. AST, total protein, and OP were identified as reliable predictors of liver fibrosis. The developed mathematical model has high sensitivity and specificity: 87.5 and 83.9 %, respectively.